Will the Scottish Cancer Target for the year 2000 be met? The use of cancer registration and death records to predict future cancer incidence and mortality in Scotland. - Sharp, L. (Nature Publishing Group, 1996)
Cancer mortality data reflect disease incidence and the effectiveness of treatment. Incidence data, however, reflect the burden of disease in the population and indicate the need for prevention measures, diagnostic services and cancer treatment facilities. Monitoring of targets mandates that both be considered. The Scottish Cancer Target, established in 1991, proposed that a reduction of 15% in mortality from cancer in the under-65s should be achieved between 1986 and 2000. Each year in Scotland approximately 8300 persons under 65 are diagnosed with cancer and 4500 die from the disease. The most common malignancies, in terms of both incident cases and deaths, in the under-65s, are lung and large bowel cancer in males, and breast, large bowel and lung cancer in females. A decrease of 6% in the number of cancer cases diagnosed in males under 65 is predicted between 1986 and 2000, whereas the number of cases in females in the year 2000 is expected to remain at the 1986 level. In contrast, substantial reductions in mortality are expected for both sexes: 17% and 25% in males and females respectively. Demographic changes will influence the numbers of cancer cases and deaths in the Scottish population in the year 2000. However, long-term trends in the major risk factors, such as smoking, are likely to be the most important determinants of the future cancer burden.